An Improved Quantitative Analysis Method for the Unequal Supply and Demand of Ecosystem Services and Hierarchical Governance Suggestions - Quanyi Liu; Binbin Lu; Weikang Lin; Jiansong Li; Yixin Lu; Yansong Duan (Land)
Quantifying the unequal supply and demand of ecosystem services (ESs) is a prerequisite for hierarchical ecological governance decisions. However, previous studies have largely overlooked the scale effect of spatially adjacent units and the role of spatial compactness in shaping inequality. To address these research gaps, this study conducted a survey in six counties within the Danjiangkou Basin in China. By adopting a moving window-based local Gini coefficient method, we quantified the inequality in the supply and demand of ESs in this region, and introduced a refined coefficient of variation to measure spatial compactness, analyzing the impact of urbanization on this inequality. The results indicate that the inequality in the supply and demand of ESs in this region is gradually intensifying. However, from a local perspective, the inequality exhibits significant spatial heterogeneity, decreasing gradually from urban centers to suburbs and rural areas, while maintaining strong spatial continuity. Furthermore, we found that urbanization is the primary factor exacerbating this inequality, while compact urban development can mitigate it. The findings of this study can provide practical guidance for cross-county ecological coordination, ecological restoration, and sustainable urban development.